2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5627534
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of bend sensor properties as applied in a glove for use in neurorehabilitation settings

Abstract: Following hand function impairment caused by a neurological disorder, the functional level of the upper extremities has to be assessed in the clinical and rehabilitation settings. Current hand function evaluation tests are somewhat imprecise. Instrumented gloves allow finger motion monitoring during the performance of skilled tasks, such as grasping objects. As a result, they provide an objective tool for evaluating slight changes in the fine motor skills of the hand. Numerous gloves are based on resistive ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Nevertheless, the overall mean absolute error of the optical sensor is less than 0.3, and this is more accurate than some reported sensors: the linear potentiometer (0.7) [44], the embedded hetero-core optic fibre sensor (0.9) [10], the resistive bend sensor (1.5) [45], and the fibre Bragg grating sensor (2.0) [11]. …”
Section: Sensor Performance Validationmentioning
confidence: 68%
“…Nevertheless, the overall mean absolute error of the optical sensor is less than 0.3, and this is more accurate than some reported sensors: the linear potentiometer (0.7) [44], the embedded hetero-core optic fibre sensor (0.9) [10], the resistive bend sensor (1.5) [45], and the fibre Bragg grating sensor (2.0) [11]. …”
Section: Sensor Performance Validationmentioning
confidence: 68%
“…The simulation program showed that the parallel resistor increased the linearity of the sensor output response but considerably decreased its slope, and thereby deteriorated the sensor resolution. Furthermore, this simulation and additional validation measurements also demonstrated that a series resistor of 33 kΩ maximally enhanced the sensor resolution [ 18 ]. However, the resulting resolution of 0.5° was dependent on the longitudinal position of the sensor with respect to the finger-joint.…”
Section: Methodsmentioning
confidence: 98%
“…In the properties of a flexible resistive sensor are investigated; it is made of conductive polymer thin films deposited on flexible substrates of polyimide. 33 In many cases, 3,6,8,10,13,14,23,34 polyester over-laminated bend sensors are also used, as by Flexpoint. 35 d. Hall-effect transducers.…”
Section: Sensors Typologiesmentioning
confidence: 99%
“…Another laboratory test has been described, with the goal to measure the impact energy of a small mass dropping from 70mm height onto the piezoelectric materials fixed to a rigid structure. 41 The importance of sensor positioning when bending is not uniform along the transducer is emphasized, 34 with reference to the case of finger bending. Indeed, a longitudinal displacement of few millimeters with respect to the finger joint modifies the bending-voltage curve of the sensor.…”
Section: Validation Testsmentioning
confidence: 99%